Analysis of Solar Power Generation Needs for Weather Stations based on ESP32 - FIRDAUS, FIRDAUS; VITRIA, RIKKI; RIFKA, SILFIA; LIFWARDA, LIFWARDA; DEWI, RATNA (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2025)
A remote weather station requires solar power system (PLTS), hence making power consumption calculation is very essential. PLTS analysis is applied to an ESP32-based weather station with low-power sensors to reduce costs. The process starts with setting up the station and PLTS without prior analysis, followed by a literature review, data collection of current and voltage from the SCC, conducting an analysis, and finally determining components recommendations. Calculations determine the need for a 12V, 4.375 Ah battery, 14.255 Wp solar panel, and a SCC with 0.46 A battery current and 0.306 A load current. Adjusted to market availability, a VRLA 12V/6Ah battery, 20 Wp solar panel, and 5A SCC module can replace the previously used 12V/7Ah battery, 50 Wp solar panel, and 10A SCC.